P214 Faecal S100A12 as a non-invasive marker of inflammatory activity in pediatric Inflammatory Bowel Disease. (27th May 2021) - Casertano, M; Cenni, S; Caprio, A M; Oglio, F; Pacella, D; Miele, E; Martinelli, M; Staiano, A; Strisciuglio, C
Abstract: Background: Calgranulin-C (S100A12) is a new faecal marker of inflammation that is potentially more specific for Inflammatory Bowel Disease (IBD) than calprotectin, since it is only released by activated granulocytes. In recent years it has been confirmed that the S100A12 has comparable sensitivity and specificity to fecal calprotectin (FC) in adult patients with IBD. The aim of our study was to evaluate concentration of faecal S100A12 and calprotectin (FC) to see which of the two tests best correlated to inflammation in IBD children. Methods: Between September 2019 and March 2020, we prospectively enrolled all IBD pediatric patients, both Crohn's Disease (CD) and Ulcerative Colitis (UC). Blood and faecal samples were collected in order to evaluate serological markers of inflammation, faecal S100A12A and FC. S100A12 and FC were determined by enzyme-linked immunosorbent assay (ELISA). Results: One hundred seventeen consecutive children, 46 (39%) with CD and 71 (61%) with UC were enrolled in the study. The mean age was 14.6 years (range:5–18), 44% female. Twenty three children were in clinical relapse (20%). No significant differences in S100 A12A levels were found between the UC and the CD groups (mean ±ds 25 ±32mcg/ml vs 34 ±27 mcg/ml respectively, p=0.22).In the UC group we found a statistically significant correlation of both calprotectin and S100A12 with CRP (r=0.253, p=0.044 and r=0.252, p=0.040, respectively). In CD group we found that both calprotectin and S100A12 correlated with hemoglobin (r= -0.343, p=0, 024; r=-0.401, p 0.008 respectively), hematocrit (r=-0.361, p=0, 046; r=-0.434, p=0.015, respectively), fibrinogen (r=0.499, p< 0, 001; r=0.325, p =0.038, respectively), and white blood cells count (r=0.309, p=0.044; r=0.394, p=0.021, respectively). Moreover, in CD group, FC correlated with CRP (r=0.431, p=0.004) and erythrocyte sedimentation rate (r=0.430, p=0.004). Finally, S100A12 correlated with platelet count both in CD and UC group (r=0.351, p=0.021and r=0.254, p=0.038, respectively) IBD children in clinical relapse had higher values ​​of S100A12 and FC than patients in remission (66±47 mcg/ml vs 43±42 mcg/ml, p=0.05 and 260±192 mg/Kg vs 166±169 mg/Kg, p=0.046, respectively) Conclusion: Our preliminary data show that both faecal S100A12 and FC are useful non-invasive biomarkers which reflect inflammatory activity of IBD children. Our future aim is to evaluate the correlation of S100A12 and endoscopic finding in order to further clarify its role in the diagnosis and the management of pediatric IBD.